A tale of two conditions: when people living with HIV meet three doses of inactivated COVID-19 vaccines - Tan, Yuting; Zou, Shi; Ming, Fangzhao; Wu, Songjie; Guo, Wei; Wu, Mengmeng; Tang, Weiming; Liang, Ke (Frontiers in Immunology, 2023)
Background: Currently data on long-term immune responses to three doses of inactivated COVID-19 vaccines among people living with HIV (PLWH) are still limited. Methods: A prospective cohort study with 13 months' follow-up was conducted among PLWH in China between March 2021 and August 2022 to evaluate the dynamics of SARS-CoV-2 specific humoral and cellular immunity against three doses of inactivated COVID-19 vaccines before the first dose until six months after the third dose vaccination, by comparing with healthy controls (HC). Results: 43 PLWH on antiretroviral therapy (ART) and 23 HC were enrolled. Compared with HC, the nAbs level among PLWH were significantly lower on day 14 after the second dose and on days 14, 30, 60, 90, and 120 after the booster dose. Among PLWH, the nAbs titers on days 14, 30, and 60 after the booster dose were significantly higher than the peak of the second dose. But on day 180 after the booster dose, the nAbs titers were similar to the peak of the second dose vaccination. Compared with HC, the frequencies of IFN-γ-secreting and TNF-α-secreting CD4+ and CD8+ T cells among PLWH were lower on days 14 and 180 after the booster dose vaccination. Among PLWH, increased T cell immunity was induced by the booster dose of vaccine and kept stable on day 180 after vaccination. Conclusions: The overall immunogenicity of three doses of inactivated COVID-19 vaccines among PLWH was lower than among healthy controls. Further strategies are needed to improve the immunogenicity to inactivated COVID-19 vaccines.